Empreendedorismo corporativo: nova estratégia para inovação das organizações - Almeida, Thalyta Damasceno Alcoforado de (2016)
Entrepreneurship drives the creation of new jobs and income generation, and many people undertake, whether by necessity to generate income for their families or to develop a career. In the last two decades, intrepreneurship has been widespread in Brazil, and the country has been increasing research addressing its growth rate. Among the forms of entrepreneurship that has grown is the corporate entrepreneurship, which has been stimulated by companies as order to win market position through innovation. Thus, one comes to the following question: corporate entrepreneur can be a key element for businesses. In view of this challenge, study has as main objective to analyze the importance of the corporate entrepreneur for business, especially when it comes to innovation as well as present some cases of companies that compatibilizaram the human factor in their organizational structures, identifying some characteristics of the entrepreneur corporate. To achieve these objectives, a literature search was conducted on the theme in question. In short, the figure of the corporate entrepreneur has been a source of many studies and research aimed at defining and quote characteristics and behavior that identify their profile and how its actions influence the projects in which they operate.